E-business and Export Behaviour Evidence from Indian Firms - K. Lal (Discussion Paper No. 2002/68, 2002)
The paper identifies and analyses the factors that influenced the export performance of firms in the post-liberalization era of the Indian economy. The study is based on primary data collected from fifty-one firms located in the national capital region. Entrepreneurial characteristics, historical data of firms, and other firm-specific factors such as size of operation, export intensity, international orientation, wage rates, and profit margins were included in the analysis. The findings of the study suggest that the performance of firms that have adopted more advanced e-business tools has been better than others in international markets, as also that size of operation has played an important role in the export performance of firms. It is found that export-oriented firms employ more skilled workforce and the labour productivity of these firms is higher than others.